The Heart of the Madder: An Important Prehistoric Pigment and Its Botanical and Cultural Roots - (:unkn) unknown (My University, 2018)
In recent years, an interest in natural botanical dye sources has prompted new research into the cultivation and processing of prehistoric dye plants. Advances in chemical analyses of ancient European textiles have provided more information about dye plants such as woad (Isatis tinctoria) weld (Reseda luteola) and madder (Rubia tinctorum), which were important sources of color in early textile production. Evidence of madder dye has been reported in the archaeological record of the European Bronze and Iron Ages in textiles preserved in the Hallstatt salt mines, Scandinavian bog sites and other elite European burials but the picture of madder usage from the Late Bronze Age into the medieval era is still unclear. The use of other indigenous plants related to madder also complicates this picture. This thesis critically reviews the history of research on madder and the evidence for its use in archaeological contexts in Europe. The experimental component of the thesis involved 1) growing madder root plants and analyzing them for growth rate, hardiness, and fecundity and 2) using madder root with and without mordants, at various temperatures and pH levels on a range of archaeologically attested textiles to determine the spectrum of red hues that could have been obtained in prehistory. This research contributes to the literature on growing and dying with madder root, its use in prehistoric textile and dye production and the significance of color in prehistory.
Keywords: Celtic; dyes; madder; rubia; textiles